Odpowiedzi

Najlepsza Odpowiedź!
2010-02-05T13:07:59+01:00
A)
a2 = 5/12 ; a3 = 2/15
q = a3/a2 = (2/15) : (5/12) = (2/15)*(12/5) = 24/75
a2 = a1*q ---> a1 = a2 /q
a1 = (5/12): (24/75) = (5/12)* (75/24) = 375/288
Odp. a1 = 375/288 oraz q = 24/75
b)
a3 = 1 ½ , a4 = 1 ¼
q = a4 / a3 =( 5/4) :(3/2) = (5/4)*(2/3) = 5/6
a3 = a1 *q² --> a1 = a3 / q² = (3/2) : (5/6)² = (3/2) : (25/36) =
= (3/2)* (36/25) = 54/25
Odp. a1 = 54/25 oraz q = 5/6
d)
a3 = -3; a4 = -24
q = a4 : a3 = -24 : (-3) = 8
a3 = a1*q²
a1 = a3 : q² = -3 : 8² = -3 : 64 = - 3/64
odp. a1 = -3/64 oraz q = 8
e)
a6 = 32; a10 = 2
a6 = a1*q⁵ oraz a10 = a1*q⁹
a1*q⁹ : a1*q⁵ = q⁴ = 2/32 = 1/16
q = 1/2
a1 = a6 : q⁵ = 32 : (1/2)⁵ = 32 :(1/32) = 32*32 = 1024
Odp. a1 = 1024 oraz q = 1/2
f)
a6 = 1 ; a8 = 9
q² = a8 : a6 = 9 : 1 = 9
q = 3
a6 = a1*q⁵
a1 = a6: q⁵ = 1 : 3⁵ = 1 : 243 = 1/243
odp. a1 = 1/243 oraz q = 3



17 2 17